Spectroscopically in situ traceable heterodyne frequency-scanning interferometry for distances up to 50 m. (1st July 2015) - Prellinger, Günther; Meiners-Hagen, Karl; Pollinger, Florian
Abstract: High-resolution saturation spectroscopy of iodine transitions at 637 nm is used to generate physically stable frequency reference markers for an interferometric absolute distance measurement based on frequency-scanning interferometry. Both experiments are performed simultaneously, posing severe challenges to the in principle well-established experimental techniques. The software-based enhancement of the signal-to-noise ratio is discussed in detail, as well as the demodulation and separation of the heterodyne interferometer signals. Verification measurements up to fifty meters indicate a relative measurement uncertainty well below 10 −6 .